Prime Ministerial Decree No. 104 for the year 2022 : Distribution of the investment activities sub sectors in the geographic scope of Sectors (A) and (B) = قرار رئيس مجلس الوزراء رقم 104 لسنة 202 : توزيع القطاعات الفرعية لأنشطة الاستثمار بالنطاق الجغرافي للقطاعين أ و ب - Egypt; The middle east library for economic services, translator. (2025)
Prime ministerial decree no. 104 for the year 2022 – schedule (1) sub-sectors of the investment activities in the geographic scope of sector (A) – schedule (2) sub-sectors of the investment activities in the geographic scope of sector (B) قرار رئيس مجلس الوزراء رقم 104 لسنة 2022 – جدول (1) القطاعات الفرعية لأنشطة الاستثمار بالنطاق الجغرافى للقطاع (أ) – جدول (2) القطاعات الفرعية لأنشطة الاستثمار بالنطاق الجغرافى للقطاع (ب)